Synthesis and Characterization of Mixed Ligand Complexes of Lanthanides(III) - PALSOKAR, S.D.; CHAVAN, M.C. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of rare earth ions La3+, Pr3+, Nd3+, Sm3+, Gd3+ and Dy3+ with ortho-vanillinmonoxime as the primary ligand and 8-hydroxyquinoline(oxine), thiourea as the secondary ligands have been prepared and characterized on the basis of their elemental analysis, electronic, infrared and NMR spectra, thermal analysis and conductivity measurements. A study of ultraviolet spectra gave an evidence about complexation. Visible spectra of Pr3+, Nd3+ and Sm3+ complexes indicated nepheIauxetic effect in these complexes. The covalency parameter and δ% covalency indicate strong interaction of lanthanide ions and the ligands. The shift in the characteristic infrared frequencies of free ligand band confirms the centres of coordination. Thermal analysis indicated the presence of coordinated water molecules. The molar conductance in DMF and DMSO indicated that the 8-hydroxyquinoline complexes behaved as non-electrolyte while the thiourea complcxes behaved as 1 : 1 electrolyte system.